Assessment of perceived barriers on online health information seeking activities among university students: case study of Malaysia - Kartiwi, Mira; Hassan Munassar, Fatima (Faculty of Information and Communication Technology, International Islamic University Malaysia, 2019)
Due to the overgrowth of the information over the internet, concept of information needs and seeking behaviors of various group of people has been raised and highlighted to be studied. Understanding user needs and behaviors can wipe half of the solving time in providing information-services. Information seeking behavior becomes the major issue highlighted by several researchers specially the students’ information seeking behavior. Previous study shows that being high education learning students, it is not guaranteed their proficiency in searching skills to retrieve the proper and valid information. There are perceived barriers that inherent to how information is seek online. Hence, it is the aim of this paper to assess the potential dimensions that emerged from a number of observational items on the perceived barriers. Two important dimensions emerged from this study of perceived barriers to eHealth information seeking activities. These are, psychological and technical barriers.